Maintenance of government school in Malaysia case study: SMK Dato' Sulaiman, SMK Penghulu Saad, SK Parit Sulong, SK Seri Chantek and SK Permatang Rengas Batu Pahat Johor / Nor Alifah Sabah@Saaban - Sabah@Saaban, Nor Alifah (2010)
The responsibilities of public property management in Malaysia including public school are fall under government department and often manage in reactive manner. The process of application on maintenance works are identified to find out the factors of it's happen. This study focus on identify the common practice of maintenance management of public school, identify the factor of late and not been carried out thoroughly of maintenance management work in public school and identify the satisfaction level with the maintenance provided. In order to achieve objectives identified, literature review was done then the data was collected using questionnaires, the collected data was analyzed using Microsoft excel. Finding had shown that although many school applied both in-house and out source maintenance management system but the condition of school still at average level which means performance fall shorts of requirement expectation and need improvement due to improper maintenance practice.